2020
DOI: 10.1186/s12964-020-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

Knocking-out the Siah2 E3 ubiquitin ligase prevents mitochondrial NCX3 degradation, regulates mitochondrial fission and fusion, and restores mitochondrial function in hypoxic neurons

Abstract: Background: Na + /Ca 2+ exchanger isoform 3 (NCX3) regulates mitochondrial Ca 2+ handling through the outer mitochondrial membrane (OMM) and promotes neuronal survival during oxygen and glucose deprivation (OGD). Conversely, Seven In-Absentia Homolog 2 (Siah2), an E3-ubiquitin ligase, which is activated under hypoxic conditions, causes proteolysis of mitochondrial and cellular proteins. In the present study, we investigated whether siah2, upon its activation during hypoxia, interacts with NCX3 and whether such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Analysis of multiple independent patient‐derived OxPhos‐ and BCR‐DLBCL indicated that, compared to BCR‐DLBCLs, OxPhos‐DLBCLs have fragmented mitochondria, as revealed by the cross‐sectional area of individual mitochondria in cells stained with MitoTracker Green, and quantification of mitochondria with a form factor (FF) < 2 (Figs 3A–C and EV4 ). Mitochondrial FF is a readout for mitochondrial branching, where reduced FF would suggest the mitochondrion is more spherical, while greater FF values would suggest highly interconnected mitochondria (Cribbs & Strack, 2009 ; Sisalli et al , 2020 ). Mitochondria in DLBCL cells were classified into short (FF ≤ 2), intermediate (2 ≤ FF ≤ 4), and long (FF > 4) morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of multiple independent patient‐derived OxPhos‐ and BCR‐DLBCL indicated that, compared to BCR‐DLBCLs, OxPhos‐DLBCLs have fragmented mitochondria, as revealed by the cross‐sectional area of individual mitochondria in cells stained with MitoTracker Green, and quantification of mitochondria with a form factor (FF) < 2 (Figs 3A–C and EV4 ). Mitochondrial FF is a readout for mitochondrial branching, where reduced FF would suggest the mitochondrion is more spherical, while greater FF values would suggest highly interconnected mitochondria (Cribbs & Strack, 2009 ; Sisalli et al , 2020 ). Mitochondria in DLBCL cells were classified into short (FF ≤ 2), intermediate (2 ≤ FF ≤ 4), and long (FF > 4) morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…Besides SIAH1, the other members of the SIAH family have been found to regulate different aspects of mitochondrial biology. For example, SIAH2 has been shown to regulate mitochondrial dynamics by controlling the degradation of Mfn1 and Drp1 in cortical neurons under hypoxia [ 106 ]. Moreover, SIAH2 negatively regulates mitochondrial biogenesis by ubiquitination and subsequent proteasomal degradation of nuclear respiratory factor 1 (NRF1), a crucial factor for mitochondrial biogenesis [ 107 ] under hypoxic microenvironments [ 108 ].…”
Section: Ubiquitin-dependent Mitophagymentioning
confidence: 99%
“…At the end of the incubation, cells were washed 3 times in the same medium. An increase in the mitochondria-localized intensity of fluorescence was indicative of mCa 2+ overload [ 21 ].…”
Section: Methodsmentioning
confidence: 99%